The Evaluation of Children Friendly School's Programs towards Banjarmasin as a Children Friendly City - Martodiryo, Suratno; Rahmatullah, Muhammad (International Journal Labs, 2022)
Background: Children Friendly Schools (CFS) are a dream for every student and parent, because in school students will get academic learning with a feeling of fun and calm. Aim: This study aims to evaluate the real conditions of primary schools in the city of Banjarmasin in the perspective of Child Friendly Schools and recommendations regarding the prototype of standard instruments and constructive criteria to measure the feasibility of schools as Child Friendly Schools with the standards set. Method: The research method uses R&D techniques with stages: needs analysis, instrument prototype development, trials for construct validation and dissemination using 31 Elementary Schools in Banjarmasin City. The instrument of data collection uses a structured questionnaire. Findings: The results of the study show that the measuring instruments for achieving Children Friendly schools include 6 (six) components, namely (1) CFS policy, (2) implementation of the learning process, (3) Trained Educators and Education Personnel on Child Rights, (4) Infrastructure, (5) children's participation, (6) participation of parents, community institutions, business world, other stakeholders. There were 15 schools (48.39%) which were still below the average score and 16 schools (51.61%) were above the average score. The highest achievement level is the Learning Process Implementation Component (93.3%) and the lowest achievement is the Child Participation Component (56.68%). Schools have not been able to optimize the role of key targets to increase children's participation in planning, policy, learning, supervision and complaints mechanisms related to the fulfillment of children's rights and protection in education.